A patient with heart failure – challenges faced by a primary care physician - Nessler, Jadwiga; Siniarski, Aleksander (Lekarz POZ, 2019)
Approximately 175,000 people die annually due to cardiovascular diseases in Poland, which accounts for 46% of all deaths. Heart failure (HF) is a consequence of myocardial damage from various cardiovascular diseases. Nevertheless, HF is caused most frequently by coronary artery disease and arterial hypertension. Furthermore, HF has become an epidemic of the 21st century. The main goal of the management of HF patients is to create a complementary system combining outpatient and inpatient healthcare. The foundations of this specific healthcare system are primary care physicians, cardiologists, and nurses specialised in the care of patients with HF. The scope of the primary care physician’s activities is very wide and focuses not only on prevention of cardiovascular risk factors that predispose to the development of HF, but also on treatment in a stable period of their disease or during the initial symptoms of decompensation. The authors present a review article that states the main assumptions of this comprehensive healthcare system and the special role of primary care physicians in the treatment and management of patients with HF. Furthermore, they demonstrate the most up-to date evidence-based data on primary, secondary, and tertiary prevention in HF.